The Development of Blended Learning Environment Model for Communicative Language Teaching Using Active Learning to Enhance Creative Communication Skill and Collaboration Skills for Undergraduate Students - วีระปรียากูร, จินตนา; กิจระการ, เผชิญ (Ratchaphruek Journal, 2019)
The objectives were to 1) study the currents problems, conditions, and requirements of the blended learning environment model for communicative language teaching using active learning to enhance creative communication and collaboration skills,2) study and develop the main factors and characters of the blended learning environment model, and 3) investigate the results of using the developed blended learning environment model for communicative language teaching using active learning to enhance creative communication and collaboration skills for undergraduate students. The results found that the 93 samples agreed with the blended learning environment model for communicative language teaching using active learning in 5 learning physical environment, psychological environment, social environment, information environment, and teaching and learning processes. The currents problems for lecturers were at a moderate level but at a high level for the students. The requirements of the blended learning environment model for communicative language teaching using active learning from lectures and students were in high level. The experts agreed with all the main factors and characters at the high level. The results of using the developed blended learning environment model for communicative language teaching using active learning to enhance creative communication and collaboration skills for undergraduate students were increased statistically significant at the level of .05. The collaboration skills by studying and completing the activities from the blended learning environment model for communicative language teaching using active learning was in high level. However, the creative communication skills, there was only one group passed by concluding the activities while the other groups obtain good scores. The students were satisfied with their good attitude to the blended learning environment model for communicative language teaching using active learning to enhance creative communication skill and collaboration skills at the high level.